Análise do processo de internalização de propostas de educação ambiental em escolas de Ensino Médio no município de Acaraú-CE - Santos, Maria Auxiliadora Ferreira dos (2008)
To insert environmental education in the school is a very hard task, although the question has been largely discussed since some years ago. The main object of this research is limited to the way the contents of Environmental Education are inserted in school programs, as well as to assert that, as a law, it must be put in practice not only because it is obligatory, but because it is important to school programs, especially to Acaraú´s primary and secondary schools, having in view the importance of the natural resources in which schools are inserted and the development of ways to solve problems related to the quality of life of the dwellers of these places. It is important the study of the law 9795/99 on Environmental Education, passed on July 25th, 2005, by means of the decree no. 4.281, established in the Municipal Organic Law and other documents ruling the Environmental Education. Our purpose is to give orientation on Environmental Education to the above-mentioned schools aiming at the permanent formation about that subject, in order to constitute, in the future, a real net between school and community and to spread out concepts about sustainability. This way, poverty conditions should be faced as environmental problems, bringing about the relationship between natural resources and poverty. The making of shrimp beds, predatory fishing, swamp degradation and irregular occupation constitute elements to this research. The theoretic terms are based upon principles of Environmental Education, area sustainability and inter-disciplinarily and trans-disciplinarily in Environmental Sciences, which have been applied under the form of capacities and the presentation of documents, projects, maps, discussions and reflections about the mass social movements as a positive consequence of the implementation of this project